Macroeconomic Factors That Affect Depositor Funds of Sharia Bank in Indonesia - Sanjaya, Sigit (Journal of Developing Economies, 2021)
This study aims to determine the effect of macroeconomic factors on Islamic bank savings funds in Indonesia. Macroeconomic variables used; economic growth, government debt, exchange rates, trade balance, money supply (M2), and foreign direct investment. Macroeconomic data is obtained from the publication of the Central Statistics Agency (BPS). Depositors' fund data is obtained from the Financial Services Authority (OJK). The population consists of all Islamic commercial banks and Islamic business units. The sampling technique used total sampling, and data analysis was performed using multiple linear regression. Observation data from January 2005 to December 2019 used quarterly data. The results show that government debt and money supply (M2) positively and significantly affect depositors of Islamic banks in Indonesia. In contrast, economic growth, exchange rates, trade balance, and foreign investment do not significantly affect Islamic bank deposit funds in Indonesia. Keywords: Macroeconomic Factors, Depositor Funds, Sharia Bank JEL: C3, E00, Z00